Together we unite: the role of the Commonwealth in achieving universal health coverage through pharmaceutical care amidst the COVID-19 pandemic - Amy Hai Yan Chan; Victoria Rutter; Diane Ashiru-Oredope; Chloe Tuck; Zaheer- (Taylor & Francis Group, 2020)
The world currently faces unprecedented health challenges as COVID-19 poses a huge threat to health systems, economies and societies as we know it. The events of the current COVID-19 pandemic have further emphasised existing issues within our health systems. There is no better time than now to come together in global solidarity to tackle these evolving threats of COVID-19 pandemic. The Commonwealth is an ideally placed network to tackle these global health challenges, with its wide-reaching networks of governmental, non-governmental and civil society organisations across all continents. Although the biennial Commonwealth Heads of Government Meeting (CHOGM) originally scheduled to take place in Kigali in Rwanda 22-27 June 2020 has been postponed in view of COVID-19, Commonwealth country discussions are continuing, centred on the CHOGM key theme of 'Delivering a Common Future: Connecting, Innovating, Transforming', and five subthemes of Information and Communications Technology (ICT) and Innovation; Trade; Environment; Governance and the Rule of Law; and Youth. The planned CHOGM and Commonwealth itself provides all members a timely platform to consider innovative ways to connect, innovate and transform healthcare to meet the needs of their populations. This commentary considers these five CHOGM subthemes and how member nations can be supported to achieve universal health coverage through optimising medicines use and outcomes, in the midst of a global pandemic in line with the global health agenda.